Endo-beta-N-acetylglucosaminidase H sensitivity of precursors to herpes simplex virus type 1 glycoproteins gB and gC. - Wenske, E A (1982)
The endoglycosidase endo-beta-N-acetylglucominidase H (endo H) was used to examine the nature of the oligosaccharides associated with the herpes simplex virus type 1 glycoproteins gA, gB, and gC. Immunoprecipitates from detergent extracts of infected cells, using monospecific antisera to gAB and gC, were treated with endo H. The low-molecular-weight precursor to gC, pgC(105), was found to be sensitive to endo H. Removal of the endo H-sensitive oligosaccharide chains from pgC(105) resulted in a protein with an apparent molecular weight of 75,000. In contrast, the fully glycosylated gC was not sensitive to endo H treatment. These results suggested that the oligosaccharide chains of pgC(105) were primarily of the simple high-mannose type. Both gA and gB were sensitive to endo H treatment; however, gB appeared to be only partially susceptible, whereas [3H]mannose-labeled gA was not detectable after endo H treatment. These results that gB contained both complex- and simple-type oligosaccharides, and gA contained only simple-type oligosaccharides. An accumulation of the high-mannose glycoproteins pgC(105) and gA was observed in monensin-treated infected cells with a concomitant inhibition of gB and gC. Glycoproteins gA and pgC(105) synthesized in the presence of monensin were also sensitive to endo H treatment.